Role of mismatch repair in the Escherichia coli UVM response. - Murphy, H S (1996)
Mutagenesis at 3,N4-ethenocytosine (epsilonC), a nonpairing mutagenic lesion, is significantly enhanced in Escherichia coli cells pretreated with UV, alkylating agents, or H2O2. This effect, termed UVM (for UV modulation of mutagenesis), is distinct from known DNA damage-inducible responses, such as the SOS response, the adaptive response to alkylating agents, or the oxyR-mediated response to oxidative agents. Here, we have addressed the hypothesis that UVM results from transient depletion of a mismatch repair activity that normally acts to reduce mutagenesis. To test whether the loss of mismatch repair activities results in the predicted constitutive UVM phenotype, E. coli cells defective for methyl-directed mismatch repair, for very-short-patch repair, or for the N-glycosylase activities MutY and MutM were treated with the UVM-inducing agent 1-methyl-3-nitro-1-nitrosoguanidine, with subsequent transfection of M13 viral single-stranded DNA bearing a site-specific epsilonC lesion. Survival of the M13 DNA was measured as transfection efficiency, and mutation fixation at the lesion was characterized by multiplex sequencing technology. The results showed normal UVM induction patterns in all the repair-defective strains tested. In addition, normal UVM induction was observed in cells overexpressing MutH, MutL, or MutS. All strains displayed UVM reactivation, the term used to describe the increased survival of epsilonC-containing DNA in UVM-induced cells. Taken together, these results indicate that the UVM response is independent of known mismatch repair systems in E. coli and may thus represent a previously unrecognized misrepair or misreplication pathway.